Effectiveness of Using Android-Based Augmented Reality (AR) Media to Enhance Students' Learning Motivation in Science Lessons - Wargo Silanto; Abdul Muis; Waris; Indah Kharismawati (Postgraduate, University of Mataram, 2025)
This study investigates the effectiveness of Android-based Augmented Reality (AR) in enhancing students' learning motivation in science. Using a quasi-experimental design, two groups were involved: a control group, which was taught using conventional methods, and an experimental group, which used AR media. The research sample consisted of 42 high school students, divided into two groups of 21 each. Data were collected through pretests and posttests, as well as a motivation questionnaire adapted from the ARCS model (Attention, Relevance, Confidence, Satisfaction). The results revealed a significant difference in motivation between the two groups, with the experimental group showing an average posttest score of 84.11, compared to 61.72 in the control group. The t-test showed a significant difference (p = 0.001), and N-gain analysis demonstrated that the experimental group had a higher N-gain (77.59%) compared to the control group (56.56%), indicating the effectiveness of AR. Additionally, the experimental group showed significant improvements in attention and satisfaction. This study concludes that Android-based AR is an effective tool for increasing student motivation in science, and recommends further research on its use in other subjects with larger samples.